Pengaruh Kebijakan Dividen, Profitabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Perkebunan yang Terdaftar di Bursa Efek Indonesia - Cintya Marisa; Isni Andriana; Kemas M. Husni Thamrin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aimed to determine the effect of dividend policy, profitability, and firm size on the value of the company of plantation companies listed on the Indonesia Stock Exchange (IDX) within period 2014-2020. The study used quantitative data type by using secondary data as the data source. The sampling in this study used the Purposive Sampling method with a sample of 5 companies. The analysis technique used is multiple linear analysis using Eviews. The results showed that dividend policy variable has significant and positive effect on firm value, profitability variable has no effect on firm value, and firm size has significant and negative effect on firm value.